Interactive Effects of Drought–Flood Abrupt Alternation on Morpho-Agronomic and Nutrient Use Traits in Rice - Jie Huang (MDPI AG, 2021)
The frequent occurrence of drought–flood abrupt alternation (DFAA) in Huaibei Plain has shown a great impact on local rice production. Pot experiments were performed in 2016–2018 to investigate the effects of co-occurring drought and flooding stresses on dry weight (DW), grain yield, nitrogen (N), phosphorus (P) and potassium (K) uptake and use efficiencies (NUE, PUE and KUE) in rice. The results showed that DFAA changed the accumulation of biomass and nutrients among different organs in rice. Compared with control, DFAA significantly reduced the grain yield (−29.8%) and root DW (−30.0%), but increased the DW in stem and leaf (10.2% and 9.7%). The root/shoot ratio and morphological size of the root system in DFAA-treated plants was smaller than those of drought alone and flooding alone. Under DFAA stresses, the specific absorption rate of N, P and K increased significantly (47.9%, 31.8% and 32.8%, respectively), while NUE, PUE and KUE decreased significantly (−27.9%, −10.8% and −19.7%, respectively). The decrease of nutrient use efficiencies was mainly due to the redundant growth of branches and leaves, and the key factor limiting grain yield under DFAA conditions was the effective utilization of N. Compared with the earlier drought, the subsequent flooding might have more influence on rice growth, nutrient utilization and yield formation, but the interaction of the two weakened the cumulative effect of drought and flooding. These findings provide a scientific basis for establishing a nutrient and water management system of rice cultivation under transient soil moisture conditions.